The efficiency of proprioceptive training in preventing injuries to team athletes: A systematic review - Marko Manojlović (Exercise and Quality of Life)
The aim of this systematic review was to evaluate the effectiveness of proprioceptive training in the prevention of lower extremity injuries, especially the ankle and knee joint, in team athletes. PRISMA recommendations were applied for this research. PubMed, ScienceDirect, and BioMed Central were used to identify relevant studies. The methodological quality of studies was assessed using the Physiotherapy Evidence Database-PEDro scale. Only 7 research met the eligibility criteria, and their outcomes were presented. Proprioceptive training has been shown to be very effective in preventing ankle injuries, especially in recurrent ankle sprains. However, in 3 of 4 studies lacked the effects of proprioceptive training in the prevention of knee and ACL injuries. Based on the results of the analyzed research, I can conclude that proprioceptive training is a very effective training tool in the prevention of ankle sprains in the population of team athletes, but proprioceptive training is not sufficient as the only training component in preventing knee injuries.